Energy Gel : a new product introduction (A) - Raviv, Artur, (SAGE Knowledge. Cases., 2017)
Presents an analysis of the decision regarding a new product introduction. The main issues for discussion are: sunk costs, incremental costs, cannibalization, shared facilities, and the treatment of inflation.